2004
DOI: 10.1111/j.0105-1873.2004.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Primula obconica– is contact allergy on the decline?

Abstract: Primula obconica, a member of the Primulaceae family, was introduced to Britain from China in 1880. P. obconica cultivars, which are reputed to contain less primin, have been developed over the past number of years in an attempt to reduce the incidence of allergic contact dermatitis. Primin (2-methoxy-6-pentyl-1,4-benzoquinone) is the main sensitizer, although other allergens have been postulated. We believe the incidence of primula allergic contact dermatitis has fallen since the introduction of primin-free P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
2
14
1
2
Order By: Relevance
“…Here, a significant decline in primin allergy was seen from 1995 to 2002 (7). Further, a telephone survey performed among selected seed suppliers and plant retailers showed that 50% of suppliers were selling primin‐free varieties, while the majority of retailers were not selling P. obconica at all (7). In Denmark, there has been a reduction in the production of P. obconica from 448 000 plants in 2003 to 175 000 in 2005.…”
Section: Discussionmentioning
confidence: 95%
“…Here, a significant decline in primin allergy was seen from 1995 to 2002 (7). Further, a telephone survey performed among selected seed suppliers and plant retailers showed that 50% of suppliers were selling primin‐free varieties, while the majority of retailers were not selling P. obconica at all (7). In Denmark, there has been a reduction in the production of P. obconica from 448 000 plants in 2003 to 175 000 in 2005.…”
Section: Discussionmentioning
confidence: 95%
“…It had a low frequency in previous studies carried out at LUTH It may be an allergen to watch due to the increasing awareness and practice of horticulture or gardening in households in Lagos. Ironically, its removal from the European series is presently being considered as there are declining positive reactions to it in the West . The response to treatment as outlined by the consensus statement on the management of hand eczema was an improvement in the severity of the dermatitis at the 6‐week follow‐up visit …”
Section: Discussionmentioning
confidence: 99%
“…The small hairs (thrycomas) present in the leaves, stems and flowers, when in contact with the skin, release a quinone known as primin, its allergen, 12 and also miconidine. 34,35 It has been considered one of the greatest causes of contact dermatitis in some regions of Europe.…”
Section: Primulaceaementioning
confidence: 99%